﻿Original descriptions of Palaearctic species of the genus Plateumaris C. G. Thomson, 1859 (Coleoptera, Chrysomelidae, Donaciinae) and their translations - Elisabeth Geiser; Remigius Geiser (ZooKeys, 2023)
Many original descriptions of beetles were published in Latin with specific idioms and technical terms, which are sometimes difficult to understand. The exact meaning of these descriptions is necessary for taxonomic and systematic research. Of the ten Palaearctic Plateumaris species regarded as valid three were described in English, the remaining seven in Latin, French, or German: P. amurensis Weise, 1898, P. bracata (Scopoli, 1772), P. consimilis (Schrank, 1781), P. roscida Weise, 1912, P. rustica (Kunze, 1818), P. sericea (Linnaeus, 1758), and P. weisei (Duvivier, 1885). These seven non-English original descriptions and their translations into English are presented here. Additionally, the translations of the first descriptions of the genus Plateumaris and of its 19 synonyms (some were described in Russian, also) are given.